Des ressources de cours libres et collaboratives pour une formation hybride des enseignants : Design et impact - Philippe Dessus; Émilie Besse (Centre National d'Enseignement à Distance, 2020)
For any team of university teachers, designing and using open educational resources (OER) is a difficult task, both because of a lack of knowledge of the license types, and because of the diversity of access types and resource use: remotely or face-to-face, in or out of class, available in a teaching platform or not. We establish here a framework for analyzing what an OER can be in considering two facets: its design and its impact, and we test this framework on our collaborative open resource system developed at the Grenoble Alpes University Teacher Training School, in the context of preservice teacher training. The results show, on the one hand, that the transition to open resources cannot be undertaken without a significant structural effort and specific skills, and, on the other hand, that the opinion stakeholders have about the "impact openness" is related, though weakly, on what they think about OER.